Objectivity in performance ranking of higher education institutions using dynamic data envelopment analysis. Issue 4 (8th April 2019) - Kumar, Anup; Thakur, Rajiv R.
Abstract : Purpose: There has been a persistent debate on measures of efficiency and ranking procedures of higher education institutions (HEIs). Deriving absolute efficiency measures and their ranking provide a critical input for the society to choose the appropriate educational institute. The purpose of this paper is to evaluate the relative performance of institutions in management education in different locations in India and propose a holistic efficiency measurement which can be applied to HEIs in general. Design/methodology/approach: This study uses dynamic data envelopment analysis (DDEA) as the primary methodology of analysis. Multiple measures of inputs and output have been defined to assess efficiency in institutions of management education. Some of the output variables used for measuring relative effectiveness are: the number of students placed, number of entrepreneurs, median CTC of placed students, total number of students passed, number of research publications, number of students and faculty who have participated in international exchange, input variables used, student intake, faculty profile, resource allocation on the development of student, faculty and staff, industry linkages, alumni network. The institutions under study are in three different locations in India, having distinct characteristics. The multiple measures of inputs and outputs defined have been used to measure efficiency, following which DDEA was used to rank the efficiency measures. Findings: Various agencies use their framework to evaluate and rank HEIs; however, they are either subjective or less researched methodologies. The proposed method acts as a new researched and objective methodology for ranking of HEIs operating across regions with different societal, economic and political contexts. Efficiency in education is of high relevance today for various stakeholders such as students, parents, industry, policy-makers and government. An objective, such as the one proposed in this paper, would be helpful in satisfying the needs of various stakeholders. Furthermore, the government has policies of allocating funds, in case of public-funded institutions, based on efficiency levels in HEIs. The measure using DDEA suggested in this study provides a better measurement of efficiency. Research limitations/implications: This research is based on the extension of DDEA with slight modification to the denominator portion of efficiency calculation. The modification is accentuated by taking an industry benchmark or government benchmark. This may lead to slight difficulty in the appropriation of input parameters. Hence, selection of appropriate input and output parameters is the key limitation. To demonstrate capabilities of the proposed approach, this framework is implemented for performance evaluation of institutions of higher education in India. Some helpful policy-making and managerial insights are derived from the numerical results. Originality/value: The uniqueness of this research is that it adds a well-researched methodology based on DDEA to measure efficiency and rank HEIs for effective assessment and benchmarking. The frameworks used so far have been either subjective or less researched methodologies.